La (in)viabilidad de la fusión de los programas sociales en el Perú - Vásquez H., Enrique (2008)
In spite of the fact that annual social investment in Peru has risen to an average of US$ 1.000 million, the limited efficacy of social programs in Peru generates an annual cost of approximately US$ 90 million plus the exclusion of at least 3,5 million children. To deal with this, this paper proposes the creation of a Social Inclusion Fund (FIS, for its initials in Spanish) based on the fusion of 49 social programs that annually spend S/. 2,52 billion from the budget.The FIS would benefit those who live in extreme poverty and its interventions would be defined according to social gaps analysis. Once these gaps are identified, they would provide an input into preparing –with civil society participation– a «road map» that facilitates the accomplishment of well-defined targets by 2011. This would encourage a results-based management that would permit closer collaboration with the private sector in executing and enabling follow-up of FIS activities. Finally, this article briefly analyzes the progress and limitations of the present government in reforming social programs.